A critique on stylistics and deviation of the scriptures - Yaacob, Solehah@Nik Najah Fadilah (2017)
There were several attempts by some Jews and Christians to explain how the biblical authors insisted that God dictated the text to Moses. However, later the intellectual journey looks at Bible with commentaries which began at 2nd century in Palestine when the interpretation done in classical commentaries in Aramaic then in Hebrew. However, in 17th century the impact of Rashi`s commentaries pointed out the first chapter of Genesis did not describe a literary sequence. In fact, the commentaries of different centuries from different countries having testimony to the common ground of understanding between them and this process is still not ending until now. According to Avigdor Bonchek the pseudo interpretation as a result of non-depth of understanding on rules of interpretation. The interpretation must work from the original Hebrew; therefore, he believes the interpretation does not depth without refer to the original source. However, this is `escapism` typical of the literary sources, due to the major problem of Bible is not the translation itself but the interpretation sources referred. Thus the paper focuses on some deviations information in the scriptures either old testament or new testament of the Bible. In addition to that, scholars have long recognized that even some of the books accepted into the canon are probably forgeries, the church has agreed that the Gospels of Mark, Mathew, Luke and John were the authentic references for the Christian principles. How about others books which consist in Bible, are they authentic? However, some believe that there was `Pseudonymous Writing` was occurred in these Gospels. In order to examine some communication barriers of non-canonical writings, the study concentrates on the comparison with the Gospel of Barnabas which has been debated on its originality.